Isolation of anticancer bioactive secondary metabolites from the sponge-derived endophytic fungi Penicillium sp. and in-silico computational docking approach - Kaliaperumal, Kumaravel; Salendra, Limbadri; Liu, Yonghong; Ju, Zhiran; Sahu, Sunil Kumar; Elumalai, Sanniyasi; Subramanian, Kumaran; M. Alotaibi, Nahaa; Alshammari, Nawaf; Saeed, Mohd; Karunakaran, Rohini (Frontiers in Microbiology, 2023)
Introduction Fungus-derived secondary metabolites are fascinating with biomedical potential and chemical diversity. Mining endophytic fungi for drug candidates is an ongoing process in the field of drug discovery and medicinal chemistry. Endophytic fungal symbionts from terrestrial plants, marine flora, and fauna tend to produce interesting types of secondary metabolites with biomedical importance of anticancer, antiviral, and anti-tuberculosis properties. Methods An organic ethyl acetate extract of Penicillium verruculosum sponge-derived endophytic fungi from Spongia officinalis yielded seven different secondary metabolites which are purified through HPLC. The isolated compounds are of averufin (1), aspergilol-A (2), sulochrin (3), monomethyl sulochrin (4), methyl emodin (5), citreorosein (6), and diorcinol (7). All the seven isolated compounds were characterized by high-resolution NMR spectral studies. All isolated compounds', such as anticancer, antimicrobial, anti-tuberculosis, and antiviral, were subjected to bioactivity screening. Results Out of seven tested compounds, compound (1) exhibits strong anticancer activity toward myeloid leukemia. HL60 cell lines have an IC50 concentration of 1.00μm, which is nearly significant to that of the standard anticancer drug taxol. A virtual computational molecular docking approach of averufin with HL60 antigens revealed that averufin binds strongly with the protein target alpha, beta-tubulin (1JFF), with a −10.98 binding score. Consecutive OSIRIS and Lipinski ADME pharmacokinetic validation of averufin with HL60 antigens revealed that averufin has good pharmacokinetic properties such as drug score, solubility, and mutagenic nature. Furthermore, aspergilol-A (2) is the first report on the Penicillium verruculosum fungal strain. Discussion We concluded that averufin (1) isolated from Penicillium verruculosum can be taken for further preliminary clinical trials like animal model in-vivo studies and pharmacodynamic studies. A future prospect of in-vivo anticancer screening of averufin can be validated through the present experimental findings.